Demonstration that fbiC Is Required by Mycobacterium bovis BCG for Coenzyme F(420) and FO Biosynthesis - Choi, Kwang-Pil (American Society for Microbiology, 2002)
Using the nitroimidazopyran-based antituberculosis drug PA-824 as a selective agent, transposon-generated Mycobacterium bovis strain BCG (M. bovis) mutants that could not make coenzyme F(420) were identified. Four independent mutants that could not make F(420) or the biosynthesis intermediate FO were examined more closely. These mutants contained transposons inserted in the M. bovis homologue of the Mycobacterium tuberculosis gene Rv1173, which we have named fbiC. Complementation of an M. bovis FbiC(−) mutant with fbiC restored the F(420) phenotype. These data demonstrate that fbiC is essential for F(420) production and that FbiC participates in a portion of the F(420) biosynthetic pathway between pyrimidinedione and FO. Homologues of fbiC were found in all 11 microorganisms that have been fully sequenced and that are known to make F(420). Four of these homologues (all from members of the aerobic actinomycetes) coded for proteins homologous over the entire length of the M. bovis FbiC, but in seven microorganisms two separate genes were found to code for proteins homologous with either the N-terminal or C-terminal portions of the M. bovis FbiC. Histidine-tagged FbiC overexpressed in Escherichia coli produced a fusion protein of the molecular mass predicted from the M. bovis BCG sequence (∼95,000 Da), as well as three other histidine-tagged proteins of significantly smaller size, which are thought to be proteolysis products of the FbiC fusion protein.